(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2025)
The article made two contributions, one methodological and one empirical. On the one hand, various indicators of institutional quality were constructed based on data from international organizations for the period 1996-2020 for a large sample of countries. On the other hand, a correlation of the indicators with an economic variable, per capita income in dollars, was carried out. The results obtained are in line with academic literature and with previous studies. High levels of institutional quality led to high levels of per capita income and vice versa. Comparing between regions, Latin America is located at low and medium levels of institutional quality, far from the countries of East Asia, Western Europe and the United States and approaching Africa. In the case of Argentina, it went from good institutions at the end of the nineties to low institutional quality in the last two decades, especially since 2010. As development theory points out, without good institutions it is not possible to grow in a sustained manner, beyond some favorable situation. Institutional bonds are not eternal.